SEAWEED AS BIOADSORBENT FOR NITROGEN AND PHOSPHORUS REMOVAL - Meirinawati, Hanny; Wahyudi, A’an Johan (Journal of Environmental Science and Sustainable Development, 2023)
Eutrophication has become a serious environmental problem because of the excessive amounts of nitrogen and phosphorus in the water. Aquaculture waste is one of the drivers of eutrophication. Seaweed is known for its ability to remove nutrients from the water. In Indonesia, research about the efficiency of seaweed in decreasing nutrient concentration in wastewater is still rare. This article reviewed the use of seaweed as an adsorbent for nitrogen and phosphorus removal. This review aims to summarize the efficiency of nutrient removal in various genera of macroalgae. The comparing bioremediation potentials of macroalgae, including growth, nutrient bioaccumulation capacity, and potential nutrient uptake, are discussed. The factors influencing nutrient uptake will also be addressed in this study. The literature was collected from ScienceDirect and Google Scholar databases. This paper found that red algae from the genus Gracilaria were the most widely used as bioremediation agents compared to other genera. This article is expected to be useful as a basis for selecting seaweed to be used as a bioremediation agent. We hope that there will be more research on seaweed as a bioadsorbent in Indonesia.